2020
DOI: 10.1002/brb3.1554
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between serum apolipoprotein B/apolipoprotein A1 ratio and brain necrosis in patients underwent radiotherapy for nasopharyngeal carcinoma

Abstract: Introduction The apolipoprotein B/apolipoprotein A1 (ApoB/ApoA1) ratio is recognized as a clinical indicator of cardiovascular disease and ischemic cerebral disease. Cerebrovascular dysfunction is also involved in head and neck radiotherapy. The aim of this study was to investigate the correlation between ApoB/ApoA1 ratio and the severity of radiation‐induced brain necrosis (RN) in patients who underwent radiotherapy after nasopharyngeal carcinoma (NPC). Methods In this retrospective study, 191 NPC patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Remarkably, the subsequent analysis found that the established LMRS model performed well in evaluating the survival outcome and drug response of HNSCCs and performed with similar efficacy to that of the 751 lipid metabolism gene model. Although not every gene was differentially expressed in the TCGA-HNSCC database, the LMRS model highlighted frequently altered genes in HNSCCs, such as IKBKB [ 32 ], MAPK9 [ 38 ], and APOB [ 34 ]. Moreover, when combined with age, gender, tumor stage, pathological classification, and smoking status, the LMRS model effectively predicted short-term and medium-term diagnostic values, surpassing other clinical parameters, such as age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the subsequent analysis found that the established LMRS model performed well in evaluating the survival outcome and drug response of HNSCCs and performed with similar efficacy to that of the 751 lipid metabolism gene model. Although not every gene was differentially expressed in the TCGA-HNSCC database, the LMRS model highlighted frequently altered genes in HNSCCs, such as IKBKB [ 32 ], MAPK9 [ 38 ], and APOB [ 34 ]. Moreover, when combined with age, gender, tumor stage, pathological classification, and smoking status, the LMRS model effectively predicted short-term and medium-term diagnostic values, surpassing other clinical parameters, such as age and gender.…”
Section: Discussionmentioning
confidence: 99%